Proton Exchange Magnetic Resonance Imaging: Current and Future Applications in Psychiatric Research - Shaffer, Joseph J.; Mani, Merry; Schmitz, Samantha L.; Xu, Jia; Owusu, Nana; Wu, Dee; Magnotta, Vincent A.; Wemmie, John A. (Frontiers in Psychiatry, 2020)
Proton exchange provides a powerful contrast mechanism for magnetic resonance imaging (MRI). MRI techniques sensitive to proton exchange provide new opportunities to map, with high spatial and temporal resolution, compounds important for brain metabolism and function. Two such techniques, chemical exchange saturation transfer (CEST) and T1 relaxation in the rotating frame (T1ρ), are emerging as promising tools in the study of neurological and psychiatric illnesses to study brain metabolism. This review describes proton exchange for non-experts, highlights the current status of proton-exchange MRI, and presents advantages and drawbacks of these techniques compared to more traditional methods of imaging brain metabolism, including positron emission tomography (PET) and MR spectroscopy (MRS). Finally, this review highlights new frontiers for the use of CEST and T1ρ in brain research.